An Analysis Characters and Theme of Bungo Stray Dogs: Beast By Kafka Asagiri - Yani Octafia; Alliefa Nassandria Suwito (Universitas Cokroaminoto Palopo, 2025)
This study is entitled An Analysis Characters and Theme of Bungo Stray Dogs: Beast by Kafka Asagiri. Purpose of this study which to analyze the intrinsic elements such as characters and its characterization, and also the theme that formed in the story. This study was designed as qualitative research by Creswell presented in the form of dialogue and text. The data are collected by analyzing the data found in a novel entitled Bungo Stray Dogs: Beast (2019) by Kafka Asagiri. This study using descriptive qualitative methods. The theories used are Wellek & Warren's concept of character, and theory of trauma by Caruth (1996) to explain the theme. The result of the study the writers find out that the main character of the novel is Akutagawa Ryunosuke and the supporting characters are Atsushi Nakajima, Osamu Dazai, and Oda Sakunosuke and also their characterization in physiological, sociological, and psychological dimensions. The themes of this novel are friendship and Teamwork: The relationship between the main characters and the members of the Armed Detective Agency shows the importance of friendship and teamwork in facing challenge, the other themes are traumatic experience by the characters such as Akutagawa's character who lived in a cruel environment, Atsushi's character with child abuse, and Dazai's trauma of losing a friend.